Re-interpretation of traditional Asian medicine with constitutional perspective - Duong Duc Pham; Seongwon Cha; Jong Yeol Kim (Integrative Medicine Research, 2013)
There has been a rapid increase in tailored medicine that emphasizes the complex inter-individual interactions, and this increase has paralleled recent significant achievements in genomics and Systems Biology. However, attempts to create a virtual human have been limited to low-levels of organization, such as gene-protein networks, due to the lack of systematic concepts at the higher levels of organisms (organ, individual, and environment). Constitutional perspective of various forms of traditional Asian medicine through the ancient, middle, and modern eras, particularly the holistic approach of Sasang constitutional medicine (SCM), may provide a novel framework for creating tailored medicine. This article aims to review the theoretical development of traditional Chinese medicine and the initiation of SCM in addition to summarizing current evidence on the genetic basis, bio-physiological features, and risk of disease of different SCM phenotypes. We also suggest that the patho-physiological principle and scientific evidence underlying SCM, particularly for the TaeEum type, can be effective in dealing with obesity-linked disease, which is a predominant disease in today's society.